Q. 405.0( 2 Votes )

# Draw the graph of

Answer :

Given equation,

x – 2y = 6

⇒ – 2y = 6 – x

For point, P (2, – 2), x = 2 and y = – 2

= – 2 = LHS

Since, RHS = LHS, therefore, (2, – 2) satisfies x – 2y = 6

For point, Q (4, – 1), x = 4 and y = – 1

= – 1 = LHS

Since, RHS = LHS, therefore, (4, – 1) satisfies x – 2y = 6

For point, Q ( – 2, – 4), x = – 2 and y = – 4

= – 4 = LHS

Since, RHS = LHS, therefore, ( – 2, – 4) satisfies x – 2y = 6

On plotting, P (2, – 2), Q (4, – 1), and R ( – 2, – 4) we get the following graph,

The blue line indicates the required graph of x – 2y = 6

It can be clearly seen from the graph, that the points P (2, – 2), Q (4, – 1), and R ( – 2, – 4) lies on the straight line

Rate this question :

<span lang="EN-USRS Aggarwal & V Aggarwal - Mathematics

The area of the tRS Aggarwal & V Aggarwal - Mathematics

The distance betwRD Sharma - Mathematics

Draw the graph ofRS Aggarwal & V Aggarwal - Mathematics

Draw the graph ofRD Sharma - Mathematics